Pyogenic granuloma-like Kaposi sarcoma: Case report and review of literature / Mardiana Abdul Aziz and Effat Omar - Abdul Aziz, Mardiana Abdul Aziz; Omar, Effat Omar (Universiti Teknologi MARA Cawangan Selangor, 2020)
Pyogenic granuloma-like Kaposi sarcoma (PGLKS) is an uncommon variant of Kaposi sarcoma (KS), which mimics benign pyogenic granuloma both clinically and histologically. We report a case of PGLKS of the toe occurring in a HIV-positive individual. It presented as a 2cm skin swelling of 2 weeks’ duration which was clinically felt to be a pyogenic granuloma. Histopathological examination revealed a polypoid atypical vascular lesion with overlying peripheral epidermal collarette. Spindle cell proliferation typically seen in KS was also identified, which was positive for human herpesvirus 8 (HHV8) by immunohistochemistry, confirming the diagnosis of PGLKS. Upon review of the literature, our case is the 29th case of PGLKS reported to date, and only the sixth in Asian population. Particular attention to histomorphology, and demonstration of HHV8 in lesional tissue will aid accurate diagnosis of this rare entity.